2022
DOI: 10.1371/journal.pone.0263766
|View full text |Cite
|
Sign up to set email alerts
|

Body self-esteem is related to subjective well-being, severity of depressive symptoms, BMI, glycated hemoglobin levels, and diabetes-related distress in type 2 diabetes

Abstract: Background There are limited data on the role of body image in patients with type 2 diabetes. The purpose of this study was to compare body self-esteem in this group with norms for the general Polish population and to investigate the relationship between body self-esteem and the psychological and clinical characteristics of the course of diabetes. Methods A group of 100 consecutive adult patients with type 2 diabetes (49 women and 51 men) aged 35 to 66 years were assessed using the Body Esteem Scale (BES), W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 55 publications
2
8
0
Order By: Relevance
“…We found that the strongest effect between diabetes and social exclusion was evident for self-esteem. In line with an earlier study 26 , people with diabetes reported lower self-esteem than people without diabetes. Self-esteem is the degree to which people have a favorable or unfavorable opinion of themselves and is significantly related to both mental and physical health 51 .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…We found that the strongest effect between diabetes and social exclusion was evident for self-esteem. In line with an earlier study 26 , people with diabetes reported lower self-esteem than people without diabetes. Self-esteem is the degree to which people have a favorable or unfavorable opinion of themselves and is significantly related to both mental and physical health 51 .…”
Section: Discussionsupporting
confidence: 91%
“…Self-esteem is the degree to which people have a favorable or unfavorable opinion of themselves and is significantly related to both mental and physical health 51 . It is considered an important psychological factor, even influencing glucose level and eventually the course of diabetes via psycho-neuroendocrine mechanisms or through stress-related unhealthy behavior 26 . This strong effect of self-esteem ties in with the results by Kato et al 2020 23 and Browne et al (2013) 52 on stigma, which report the perception of being responsible for having diabetes and considering the diagnosis a personal failure as the most prevalent aspects of stigma in diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shuyue compiled the Couple Support Questionnaire by Shuyue [ 18 ] in 2008 to measure spousal support obtained in marriage relationships. The scale is divided into 2 dimensions, subjective and objective, with a total of 18 items.…”
Section: Objects and Methodsmentioning
confidence: 99%
“…In diabetesrelated stigma, the impact of self-stigma is intertwined with social influences (Liu et al, 2017). Thus, Consequently, individuals with diabetes may be inclined to conceal their condition, fearing societal stigmatization (Kokoszka et al, 2022;Puhl et al, 2020). This situation negatively affects the physical health of the individual as well as the psychological effects (Cho et al, 2022;Harper et al, 2018;.…”
Section: Introductionmentioning
confidence: 99%